Pemanfaatan Teknologi Cerdas Untuk Pelayanan Publik: Study Tentang e-Government Dan Smart City Berbasis ICT Big Data Dan AI - Mozin, Sri Yulianty; Abdullah, Susanti; Sawali, Nadia (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study explores efforts to enhance public service efficiency through the implementation of digital technology in local government systems. The focus is on the application of e-Government as a strategy for modernizing public service delivery, particularly within the context of local governance in Indonesia. Using a qualitative approach and literature review method, this article analyzes the effectiveness of e-Government in improving transparency, accountability, and citizen participation. The findings indicate that the utilization of information and communication technology (ICT) in public services can accelerate administrative processes, reduce bureaucratic inefficiencies, and strengthen public trust in government institutions. However, challenges such as infrastructure readiness, human resource capacity, and unequal access to technology remain significant barriers that must be addressed to optimize e-Government implementation.